Compound and Non Homogeneous Poisson Software Reliability Models - Barraza, Néstor Rubén (2010)
The efficiency of two Software Reliability growth models are analyzed. The most popular based on a non homogeneous Poisson process and the less known based on a compound Poisson process. Several experimental data are used in order to analyze the goodness of fit of both models. The importance of the estimation method for the parameters involved is also analyzed.